2006
DOI: 10.1007/s11119-006-9000-2
|View full text |Cite
|
Sign up to set email alerts
|

Algorithms for sensor-based redistribution of nitrogen fertilizer in winter wheat

Abstract: Several methods were developed for the redistribution of nitrogen (N) fertilizer within fields with winter wheat (Triticum aestivum L.) based on plant and soil sensors, and topographical information. The methods were based on data from nine field experiments in nine different fields for a 3-year period. Each field was divided into 80 or more subplots fertilized with 60, 120, 180 or 240 kg N ha )1 . The relationships between plot yield, N application rate, sensor measurements and the interaction between N appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Lammel et al (2001) point out that the Yara N-sensor is valuable to avoid over-and under fertilization within a field resulting in increased yield, decreased lodging and more homogenous ripening. Other researchers accentuate that usage of the N-sensor only have resulted in small differences in yield (Berntsen and Thomsen et al 2006;Jørgensen et al 2006) and Zillmann et al (2006) point out that the N-sensor technology work when nitrogen is the main growth-limiting factor. The usage of Yara N-sensor reduces nitrogen leaching if areas with lower requirements for nitrogen fertilization within the field can be identified (Delin and Stenberg 2014).…”
Section: Experiences From Swedenmentioning
confidence: 99%
“…Lammel et al (2001) point out that the Yara N-sensor is valuable to avoid over-and under fertilization within a field resulting in increased yield, decreased lodging and more homogenous ripening. Other researchers accentuate that usage of the N-sensor only have resulted in small differences in yield (Berntsen and Thomsen et al 2006;Jørgensen et al 2006) and Zillmann et al (2006) point out that the N-sensor technology work when nitrogen is the main growth-limiting factor. The usage of Yara N-sensor reduces nitrogen leaching if areas with lower requirements for nitrogen fertilization within the field can be identified (Delin and Stenberg 2014).…”
Section: Experiences From Swedenmentioning
confidence: 99%
“…They showed variable-rate N applications would result in significant N savings compared to uniform N application, when using N priced at $0.55 kg −1 . Researchers in Europe and elsewhere (Schroder et al, 2000;Olfs et al, 2005;Berntsen et al, 2006;Tremblay and Belec, 2006;Zillmann et al, 2006) have also shown that this approach can be used to direct variable in-season N applications in cereal grains that improves NUE, crop harvest ability, and/or quality. Some of the aforementioned research involved use of the Yara N sensor system for variable N applications, which has been available for about a decade in Europe (Yara UK Limited, Lincolnshire, UK) as a commercialized service, and is being adopted by growers.…”
Section: Ground-based Remote Sensingmentioning
confidence: 99%
“…One practical manner in which to apply N uptake maps produced through the models presented in this study could be to first determine a field average N requirement according to common practice (taking the above aspects into consideration), and then redistribute the average N according to the N uptake map. This redistribution need to take into account if other factors than N is expected to limit crop growth, but generally it has been demonstrated that a reasonable approach might be to move N from areas with the lowest and highest values to medium areas (Berntsen et al 2006), and algorithms built into some tractor-borne N sensors work this way (Söderström et al, 2004). Linear relationships between N uptake and N rate to apply have been reported (Flowers et al 2003), but these have been found to be highly unreliable and often site-specific (Samborski et al 2009).…”
Section: Improvements Through Design-based N Sensor Measurementsmentioning
confidence: 99%